Experimental study of self-powered electronic circuits for piezoelectric energy harvesting: paper presented at a conference held on 14-16 July 2015 at Elephant Hills Resort, Victoria Falls, Zimbabwe - Nechibvute, Action; Chawanda, Albert; Luhanga, Pearson (Midlands State University, 2016)
Theme: 1st International Research Conference On Driving Socio-Economic Development Through Value Addition And Sustainable Use Of Resources. Sub Theme: Science and technology and sustainable development- computational sciences, nano-biotechnology, information technology